Genetic Dissection of Root Formation in Maize (Zea mays) Reveals Root‐type Specific Developmental Programmes - HOCHHOLDINGER, FRANK (Ann Bot, 2004)
• Background Maize (Zea mays) forms a complex root system comprising embryonic and post‐embryonic roots. The embryonically formed root system is made up of the primary root and a variable number of seminal roots. Later in development the post‐embryonic shoot‐borne root system becomes dominant and is responsible together with its lateral roots for the major portion of water and nutrient uptake. Although the anatomical structure of the different root‐types is very similar they are initiated from different tissues during embryonic and post‐embryonic development. Recently, a number of mutants specifically affected in maize root development have been identified. These mutants indicate that various root‐type specific developmental programmes are involved in the establishment of the maize root stock. • Scope This review summarizes these genetic data in the context of the maize root morphology and anatomy and gives an outlook on possible perspectives of the molecular analysis of maize root formation.